Large change in perpendicular magnetic anisotropy induced by an electric field in FePd ultrathin films - Bonell, F.; Murakami, S.; Shiota, Y.; Nozaki, T.; Shinjo, T.; Suzuki, Y. (Applied physics letters, 2011)
The magnetic properties of FePd ultrathin films and their variation under the influence of an electric field are investigated by magneto-optical Kerr effect (MOKE) measurements. L 1 0 -ordered FePd shows a spin reorientation transition when varying the thickness. The easy axis of magnetization is found to be normal to the plane at thicknesses above 9 monolayers (MLs) and in-plane below 9 ML. The coercive field, the perpendicular magnetic anisotropy and the MOKE signal at saturation vary with the applied electric field. The sensitivity of the interface magnetic anisotropy is estimated to be 602 fJ/Vm.